Direct growth of a graphitic nano-layer on optical fibers for ultra-fast laser application. Issue 82 (10th November 2017) - Yang, Conghao; Yun, Ling; Qiu, Yang; Dai, Hanqing; Zhu, Detao; Zhu, Zhijia; Zhang, Zuxing; Yu, Kehan; Wei, Wei
Abstract : A clean and uniform graphitic nano-layer (GNL) is grown in a controllable manner on the fiber-end by plasma-enhanced chemical vapor deposition. Using the GNL coated fiber, 991 fs soliton pulse generation at 1559 nm is achieved. Abstract : Direct growth of graphitic nano-layer (GNL) on optical fiber is achieved using plasma-enhanced chemical vapor deposition. Clean and uniform GNL nanocrystalline flakes are grown in a controllable manner on the fiber-end without catalysts. 991 fs soliton pulse generation at 1559 nm is achieved using the GNL coated optical fiber in an erbium-doped fiber laser.